DETERMINATION OF TEMPERATURE-TIME PARAMETERS OF GROWING SINGLE CRYSTALS β-BaB2O4 BY MODIFIED CZOCHRALSKI METHOD - S. A. Guretskii; I. M. Kolesova; A. V. Kravtsov; A. A. Linkevish; K. L. Trukhanava; V. B. Malyutin; V. L. Kolpashikov; S. YU. Yanovsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The aim of this work is to find of the mechanism the determination of optimal temperature-time mode of crystallization during the whole process of β-BaB2O4 crystal growth by modified Czochralski method. The phase diagram of the BaB2O4-Na2O system in the temperature range of β-BaB2O4 crystal growing is taken as a basis. The regularities of the constant geometric size crystals growth depending on the crystal-forming oxides concentration, the drawing and cooling rates and the slope of liquidus were established. The described algorithm of calculation allows to choose an optimum time-temperature crystallization mode during the whole growth process.